PELAYANAN KESEHATAN UNTUK NARAPIDANA KELOMPOK RENTAN - Subroto, Mitro; Sihombing, Arief Johannes (Ensiklopedia Sosial Review, 2024)
Vulnerable prisoners, including the elderly, persons with disabilities, pregnant and breastfeeding women, and children, require special attention in healthcare services within correctional facilities (Lapas). This group often faces higher health risks compared to other prisoners, making it essential for the correctional system to ensure that they have adequate access to healthcare services. This study aims to analyze the extent of healthcare services provided to vulnerable prisoners and to identify the obstacles faced in its implementation. The method used in this research is a literature review, where the author examines various relevant literature and regulations to obtain a comprehensive picture of the healthcare conditions in Lapas. The results indicate that healthcare services for vulnerable prisoners are not yet optimal. Several challenges include limited medical facilities and infrastructure, a lack of professional healthcare personnel, and insufficient budgets allocated for healthcare services in Lapas. Additionally, not all prisoners receive health financing guarantees, which are often only available to those classified as poor. This creates a gap in fulfilling the right to health for prisoners, which should be guaranteed by law. Therefore, concrete steps are needed to improve the quality of healthcare services, including the provision of adequate facilities and an increase in the number of medical personnel. To address these issues, systematic efforts to enhance healthcare services in Lapas are necessary. This includes a larger budget allocation, the provision of adequate healthcare facilities, and an increase in the number of trained healthcare personnel. Furthermore, it is important to implement a special housing separation system for vulnerable prisoners to ensure their safety and comfort. With these measures, it is hoped that the rights of vulnerable prisoners can be adequately fulfilled, allowing them to receive healthcare services that are fair and equivalent to those in the general community. This effort will not only improve the quality of life for prisoners but also support their rehabilitation and reintegration goals into society after serving their sentences.KeywordsHealthcare services; vulnerable prisoners; correctional facilities.